What is the role of spatial processing in the decline of episodic memory in Alzheimer’s disease? The “mental frame syncing” hypothesis - Serino, Silvia; Riva, Giuseppe (Frontiers in Aging Neuroscience, 2014)
The current theories on episodic memory suggest a crucial role of spatial processing for an effective retrieval. When prompted by a retrieval cue, the full past scene can be retrieved through the process of pattern completion. Thanks to retrosplenial cortex, this allocentric representation is translated to an egocentric representation in the medial parietal areas via information updating from other cells: place cells inform the viewpoint location, head-direction cells the viewing direction, and grid cells the self-motion signals. Based on several evidence, we argue that a crucial role for an episodic retrieval is played by a "mental frame syncing" between the allocentric view-point dependent representation and the allocentric view-point independent representation. If the mental frame syncing stops, even momentarily, it is difficult to reconstruct a coherent representation for an effective episodic recall. This is what apparently happens in Alzheimer's disease: a break in the “mental frame syncing” between these two kinds of allocentric representations, underpinned by damage to the hippocampus, may contribute significantly to the early deficit in episodic memory.